Impact of Burnout on Organizational Outcomes, the Influence of Legal Demands: The Case of Ecuadorian Physicians - Ochoa, Paola (Frontiers in Psychology, 2018)
Interest in burnout has developed extensively worldwide, but there is scarce the literature regarding the consequences that new legal demands have on burnout and on organizational outcomes in physicians. The global context of the medical profession has been characterized in the recent years by changes in the employment patterns, profound intensification of work, and increment of labor flexibility. In this context, the study aims to analyze the influence of burnout on organizational outcomes in physicians, depending on new legal demands perception in Ecuador. Regarding the method, the research was cross sectional and in the first stage, studied the psychometric characteristics, validity and reliability of the instrument to assess burnout through a series of confirmatory factor analyses. In a second part, we assessed, the robustness of the model of causal relations between the burnout dimensions and organizational outcomes. We carried out a series of path analysis, structural equation model. The study was accomplished in five hospitals and the sample was incidental, comprising 435 physicians from Ecuador. We divided the group in two subcategories, sample A, composed by participants that considered that new Criminal Code (COIP) affects them and the sample B, the group of physicians who believed that the COIP does not affect them. Burnout was assessed with the Spanish adaptation of the Maslach Burnout Inventory, the Organizational outcomes were measured with a seven-item self-report questionnaire, and we included an item regarding to the influence of new Criminal Code. We formulated four hypotheses, that considered that physicians who believed that the COIP affect them experience a greater negative influence of burnout on organizational outcomes. The results indicated that the group of physicians who believed that the COIP affects them (Sample A) experienced a greater negative influence of cynicism on productivity than Sample B. Moreover, the lack of efficacy dimension had more positive influence on turnover in group that believed that the Criminal Code does not affect their practice. The study is unique because incorporated new legal demands to traditional relation burnout and organizational outcomes in physicians.